OPTIMALISASI ALTERNATIF PRODUK SAYUR DAN PEMASARAN BERBASIS ON-LINE - Wijayanto, Adi; Lani, Ahmad (JPM Pambudi, 2017)
Tomato (Lycopersicum esculentum L.) is the most popular vegetables in the world. Softening and decay are the main factors of post-harvest losses caused by microbes Alternaria tenuis marked black spots Microorganisms enter through cracks and sores on the tomatoes. The wholesale vegetable seller group in Karangploso have difficulty when faced with the harvest of vegetables, especially tomatoes, the difficulties encountered when the amount of commodity is plentiful but the buyer is not much. This resulted in a vegetable stock is also abundant that eventually decay so sellers mangalami financial losses. Vegetable wholesaler of Commerce business management IbM1 Partners is managed by the simple management, and with the information by word of mouth for marketing, so marketing results can not be maximized. While partners IbM2 Partners also have the same problem, but it has solutions to problems but is constrained by the science and technology of food processing tomato base material. Partners for the assistance given IbM1 is (a) training of products from basic ingredients of tomato, (b) a comparative study into food production center of apple ingredients to Kota Wisata Batu and vegetable marketing website creation. While IbM Partner 2 (a) training the manufacture of products from raw material tomatoes in food / beverage to another, (b) a comparative study into food production center of apple material in Kota Wisata Batu. Manufacture of products derived from tomatoes may have a positive impact in the economy of the groups greengrocer, where tomatoes are unsold and has not experienced decay will soon be converted into other foods such as tomatoes dates, juice tomatoes, tomato jam, jelly / candy tomato and has a level of durability compared with the tomatoes in the form of vegetables. The positive impact in terms of marketing online through the website is an increasing number of buyers from all over the city that could eventually increase the economic value of the vegetable wholesalers.